The Effect of Training Given To The Caregivers of The Patients Receiving Hemodialysis Treatment on The Care Burden and The Patients’ Quality of Life: A Quasi- Experimental Study - Betül Bayrak; Birsel Demirbağ (Middle Black Sea Journal of Health Science, 2026)
Objective: To evaluate the effect of structured training in home given by the nurse to the caregivers of the patients receiving hemodialysis treatment on the care burden of the caregivers and the patients’ quality of life.Methods: This study employed a single-group quasi-experimental pre-post-test design. The study was conducted with 35 caregivers of patients undergoing hemodialysis treatment. The data were collected using a Patient and Caregiver Information Forms, the Barthel Index, the SF 36 Scale, the Zarit Caregiver Burden Scale and Training Booklet designed by the researcher. The caregivers were made a pre-post test, individual nursing interventions including a total of 5 home visits and training. Descriptive statistics, Wilcoxon and Paired Samples t tests, Pearson and Spearman correlation, Mann Whitney U and Kruskal Wallis tests, analysis of variance were used in the analysis of the data.Results: As a result of a statistically significant relation was found between pre- and post-training periods in terms of caregiver burden and quality of life of patients. It was determined in our study that as the caregiver burden decreased, the quality of life of the patients, especially regarding pain, increased.Conclusion: It was observed that training for home caregivers of patients undergoing hemodialysis treatment reduced their care burden and improved patients' quality of life. This study is an important study to demonstrate the positive effect of home visits and individual-specific interventions performed by nurses for hemodialysis patients and their caregivers.